2015
DOI: 10.1111/jog.12725
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of superimposed pre‐eclampsia, and improvement in umbilical artery flow in a surviving twin after intrauterine demise of its co‐twin

Abstract: Pre-eclampsia has a progressive clinical course, and is only cured by delivery of the placenta. We report a 30-year-old G1P0 with dichorionic twins, discordant growth and chronic hypertension who developed superimposed pre-eclampsia in her 21st week of gestation. After intrauterine demise of the severely growth-restricted twin, the superimposed pre-eclampsia resolved. The surviving twin initially had absent end diastolic flow, which resolved after the demise. A healthy 1935-g neonate with Apgar 9/9 was deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Most reports present cases of reduction on fetal indication. A few cases described lessening or resolution of pre-eclampsia after intrauterine fetal death of one fetus in a multiple pregnancy complicated by pre-eclampsia 5–8. We performed a literature search on recovery of pre-eclampsia after multifetal pregnancy reduction, of which after selection on title and abstract remained six full-text paper with a total of eight cases9–14 (table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most reports present cases of reduction on fetal indication. A few cases described lessening or resolution of pre-eclampsia after intrauterine fetal death of one fetus in a multiple pregnancy complicated by pre-eclampsia 5–8. We performed a literature search on recovery of pre-eclampsia after multifetal pregnancy reduction, of which after selection on title and abstract remained six full-text paper with a total of eight cases9–14 (table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the extreme early pregnancy and the severity of the maternal disease with increased risk of maternal morbidity and neonatal morbidity and mortality, she and her partner were counselled about termination of pregnancy on maternal indication. In addition, they were counselled about fetal reduction of the monochorionic couple resulting in a singleton pregnancy, thus reducing placental load and possibly improving her clinical condition of pre-eclampsia 5–8. She and her husband opted for the reduction of the monochorionic couple of the triplet which was performed at 16 weeks and 3 days of gestation by intracardiac infusion of potassium chloride in one of the monochorionic twins after which both fetuses deceased.…”
Section: Treatmentmentioning
confidence: 99%
“…In twin pregnancies, as compared with singletons, there is a higher incidence of pre‐eclampsia – which also tends to develop earlier and to be more severe. Some reports describe resolution of severe pre‐eclampsia after single fetal demise or the selective fetocide of a severely growth‐restricted twin followed by a favourable outcome for the surviving twin. In such cases, it is assumed that the placental involution and death following the fetal death and thereby the cessation of the placental production of whatever factor or factors led to the pre‐eclampsia are the causes of its resolution …”
Section: Discussionmentioning
confidence: 99%
“…Few cases of resolution of preeclampsia after spontaneous intrauterine death of one twin or selective termination of a dichorionic pregnancy have been reported ( 1 , 6 , 7 ) . Narasimhulu et al ( 8 ) reported resolution of superimposed preeclampsia in a surviving fetus after the intrauterine demise of its co-twin and suggested that placental involution after fetal demise was the key to resolution of preeclampsia (resolution period take 1 to 3 weeks). However, according to our cases, even if the fetus dies, preeclampsia could not be curable unless placental seperation occurred.…”
Section: Discussionmentioning
confidence: 99%